The magnificent Lizzie Brown and the ghost ship - Lockwood, Vicki; Hans, Stephanie (North Mankato, Minnesota Stone Arch Books, a Capstone imprint, 2016)
Fitzy's Circus is invited to perform at Whitby by the Maharaja Duleep Singh, but they find the locals nervous and unfriendly, worried by the ghost ship that is apparently haunting the harbor of the small seaside town--and when a valuable necklace goes missing, the circus performers are immediately suspected, so it is up to Lizzie to use her psychic abilities to discover the true criminals
English stories
a gift from book africa
1 2 13 15
Keywords: Circus -- Juvenile fiction; Psychic ability -- Juvenile fiction